Removal of Colored Organic Pollutants from Wastewaters by Magnetite/Carbon Nanocomposites: Single and Binary Systems - Simona Gabriela Muntean; Maria Andreea Nistor; Eliza Muntean; Anamaria Todea; Robert Ianoş; Cornelia Păcurariu (Journal of Chemistry)
This work develops a methodology for selective removal of industrial dyes from wastewaters using adsorption technology based on magnetic adsorbents. The magnetic nanoparticles embedded within a matrix of activated carbon were tested as adsorbents for removal of industrial dyes from aqueous solutions. The effects of four independent variables, solution pH, initial concentration of pollutant, adsorbent dose, contact time, and their interactions on the adsorption capacity of the nanocomposite were investigated in order to optimize the process. The removal efficiency of pollutants depends on solution pH and increases with increasing the carbon content, with initial concentration of the pollutants, the temperature, and the dose of magnetite/carbon nanocomposites. Pseudo-second-order kinetic model was fitted to the kinetic data, and adsorption isotherm analysis and thermodynamics were used to elucidate the adsorption mechanism. The maximum adsorption capacities were 223.82 mg g−1 for Nylosan Blue, 114.68 mg g−1 for Chromazurol S, and 286.91 mg g−1 for Basic Red 2. The regeneration and reuse of the sorbent were evaluated in seven adsorption/desorption cycles. The optimum conditions obtained for individual adsorption were selected as starting conditions for simultaneous adsorption of dyes. In binary systems, in normal conditions, selectivity decreases in the order: Red Basic 2 > Nylosan Blue > Chromazurol S.